EIT enhanced self-Kerr nonlinearity in the three-level lambda system under Doppler broadening - Khoa, Dinh Xuan; Doai, Le Van; Trong, Pham Van; Cuong, Tran Manh; Sau, Vu Ngoc; Bang, Nguyen Huy; Anh, Le Nguyen Mai (Communications in Physics, 2014)
Using density-matrix theory, an analytical expression of the self-Kerr nonlinear coefficient of a three-level lambda EIT medium for a weak probe light is derived. Influences of the coupling light and Doppler broadening on the self-Kerr coefficient are investigated and compared to experimental observation with a good agreement. The self-Kerr nonlinearity is basically modified and greatly enhanced in the spectral region corresponding to EIT transparent window. Furthermore, sign, slope, and magnitude of the self-Kerr coefficient can be controlled with frequency and intensity of the coupling light and temperature. Such controllable Kerr nonlinearity can find interesting applications in optoelectronic devices working with low-light intensity.